Crossing the Divide: Foundations of a Theology of Migration and Refugees - Groody, Daniel G. (Theological studies, 2009)
Examining theological reflection in an age of migration, the author focuses on four foundations of a theology of migration and refugees: (1) Imago Dei: Crossing the Problem—Person Divide; (2) Verbum Dei: Crossing the Divine—Human Divide; (3) Missio Dei: Crossing the Human—Human Divide; and (4) Visio Dei: Crossing the Country—Kingdom divide. As a call to cross borders and overcome barriers, migration is a way of thinking about God and human life and an expression of the Christian mission of reconciliation.